CNC Machine System Via STEP-NC Data Model and Lab VIEW Platform for Milling Operation - Minhat, Mohamad (2013)
CNC or Computer Numerical Control is a system that using CAD, CAPP, CAM and CNC called CAx chain for machining processes from design up to production stage. The Milling operation is one of the modern CNC systems for the machining processes for material removal and operated on the principle of rotary motion. Currently, ISO 6983 standard or GIM code is used as a data model for the CNC system, however, this programming language does not explicitly relate to each other to have control of arbitrary locations other than the motion of the block-by-block. As a solution, STEP-NC is a new implementation in CAx chains for manufacturing technology to replace a current standard. It plays a key role in the field of advanced manufacturing. In this paper STEP-NC data model part 10, 11 and 111 for milling are discussed and an open architecture of the controller via LabVIEW is proposed. In this proposed framework involved software and hardware platform. In order to integrate data between interpreter and LabVIEW of the data exchange platform realization methodology for the CNC system is determined in the mode of "offline." As a result, an open CNC controller system is successfully integrated for 3-axis milling machine.